Analisis Faktor Kesulitan Belajar Siswa Kelas XI SMA Negeri 11 Padang dalam Mata Pelajaran Ekonomi - Fadilla Yessa; Jean Elikal Marna (Jurnal Salingka Nagari, 2022)
This study aims to analyze the factors that cause students' learning difficulties in learning economics. This type of research is descriptive quantitative research. The population in this study were all students of class XI IPS SMA Negeri 11 Padang in the academic year 2021/2022, totaling 100 students and the sampling technique used was proportional random sampling. The data were obtained using a questionnaire with a Likert scale which was distributed to 80 students who carried out economics learning. The data obtained were processed by descriptive analysis and exploratory factor analysis. The results showed that there were 7 factors causing student learning difficulties, namely ability factors, ADHD disorders factors, learning methods factors, learning interest factors, self-confidence factors, teacher teaching style factors, and social environmental factors. Based on the results of the study, it is suggested that students, schools or teachers can work together so that learning can run well.